2020
DOI: 10.1039/d0ra01479f
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of CuO nanoparticles using Lantana camara flower extract and their potential catalytic activity towards the aza-Michael reaction

Abstract: Aza-Michael addition is one of the most exploited reactions in organic chemistry. It is regarded as one of the most popular and efficient methods for the creation of the carbon-nitrogen bond, which is a key feature of many bioactive molecules. Herein, we report the synthesis of CuO nanoparticles by an alkaline hydrolysis process in the presence of the flower extract of Lantana camara, an invasive weed, followed by calcination in air at 400 C. Microscopic results indicated that the plant extract played an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 56 publications
4
61
0
Order By: Relevance
“…with a wide range of reductive capacities acting as reducing as well as stabilizing agents during green synthesis. In the past, green synthesis of CuO nanostructures using different plant extracts such as Bauhinia tomentosa (leaf) [13], Euphorbia pulcherrima (flower) [14], Madhuca longifolia (flower and seed) [15], Lantana camara (flower) [16], Capparis spinosa (leaf) [17], Aloe vera (leaf) [18], Allium cepa, L. (peel) [19], and banana peel [12] have been demonstrated. In this study, we investigated the use of the water extract of waste papaya peel as reducing and stabilizing agents for the synthesis of copper oxide nanoparticles (CuO NPs).…”
Section: Introductionmentioning
confidence: 99%
“…with a wide range of reductive capacities acting as reducing as well as stabilizing agents during green synthesis. In the past, green synthesis of CuO nanostructures using different plant extracts such as Bauhinia tomentosa (leaf) [13], Euphorbia pulcherrima (flower) [14], Madhuca longifolia (flower and seed) [15], Lantana camara (flower) [16], Capparis spinosa (leaf) [17], Aloe vera (leaf) [18], Allium cepa, L. (peel) [19], and banana peel [12] have been demonstrated. In this study, we investigated the use of the water extract of waste papaya peel as reducing and stabilizing agents for the synthesis of copper oxide nanoparticles (CuO NPs).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of CuO nanoparticles can be used for different purposes. For example, Adiantum lunulatum was used to synthesize CuO to use as a plant defense booster [38], Lantana camara flower extract was used to enhance CuO catalytic and recyclability properties in an aza-Michael addition reaction [39], while Caesalpinia bonducella seed extract was used to synthesize a suitable CuO sensor for the electrochemical detection of riboflavin [40]. Other plant extracts were used to manufacture NiO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…CuO NPs have applications in photocatalysis [29], as an antimicrobial [30], in biomedical industry [31], as a gas sensor [32], as solar cells [33], and as batteries [34]. Reports have shown that CuO NPs have the capacity of catalyzing the reduction of 4-NP [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%